Pilot study to screen alleles under selection related to drought tolerance in banana - Breton, Catherine; Cenci, Alberto; Roux, Nicolas; Rouard, Mathieu; Carpentier, Sebastien (2020)
In banana, most of the edible cultivars are hybrids from one or both major wild diploid ancestors: Musa acuminata (A genome, 2n=2x=22) and Musa balbisiana (B genome, 2n=2x=22). These cultivars have been assigned to different genomic groups according to the number of chromosomes sets (subgenomes) and the species that donated them, e.g. AAA, AAB and ABB (2n=3x = 33). Variability in subgenome contribution to triploid clones makes pertinent to investigate the differential gene expression of Musa cultivars, in particular since genotypes with B subgenomes can be more tolerant to abiotic stresses than those containing only A subgenomes. Due to the increasing power of high-throughput genotyping and transcriptomic methods, associated with the development of genetic and statistical analysis tools, significant knowledge gains have been generated for diploid species, [2], but on polyploids analysis it is still challenging [1,3]. Polyploidy can affect the phenotype creating complex interactions between loci or alleles, such as dominance or epistasis, or through allelic dosage. This represents an additive effect of multiple copies of the same allele. Collecting information of allelic dosage allow to describe a more realistic representation of the effect of each genotype. The present pilot study describes the methodology to analyse and select Single Nucleotide Polymorphism (SNP) alleles in two conditions (drought stressed and control) on triploid Musa acuminata AAA, ABB and AAB genotypes. A SNP database developed under both conditions provided an opportunity for such allele detection and to study the nonsynonymous SNPs (substitutions altering the amino acid sequence of a protein) and synonymous SNPs (which do not affect amino acid sequence). These nonsynonymous substitutions could affect the response to a stress as drought. The nonsynonymous and synonymous substitution rates (Ka/Ks) indicate the direction of natural selection. The prediction of both positive (diverging) and negative (purifying) selection pressure on genes could provide the picture detail of evolutionary selection pressure linked to the allele dosage.